From Teaching to Curation : Cross-pollination as a Reparative Strategy in Pedagogical Field(s) of Dance - Moraes, Janaína; Bagheri Nesami, Maryam (Stockholm University Press, 2025)
This chapter is a song. We invite you to chant it out loud. It exposes issues of colonial thinking within teaching practice. Coming from two different countries, Iran and Brazil, in distant continents within the global south, we realise our ex-centricity as dance artists-academics when we are brought together by the sense of displacement with/through teaching in academia. This co-written chapter is a practice of cross-pollination: a method of nomadic/counter authorship that we have been developing through our collaborations as dance artists, curators and academics. In this chapter, we depart from the question “how can teaching be(come) a curatorial practice?” and then we unfold “what do we mean by curation?” and “how can we teach/learn through curationship?” Understanding the curatorial practice as a practice of caring for/with/through relationships with an ‘other’, we step into counter-colonial practices of curation by celebrating the multiple and the multitude, poly relations that engage in response to situated territories, in a co-laboration of spiral relationships. To think of curationship as experiences of confluence is to value ecosystems of care that takes place through co-learning, experimenting, conversing, and co-curating as we re:pair our senses of belonging with place, time, and relations.
Keywords: koreografia; kuratointi